Active-Knowledge-Sharing-Method through High School Students at Kalimantan Tengah - Eukaristia, Lian; Wadibar, Dorthea Aryani; Winathae, Rendy; Lukas, Lukas (Al-Hijr: Journal of Adulearn World, 2023)
The purpose of this paper is to explain that learning is the main activity in the whole educational process in schools. Learning is a process to achieve the success of educational goals in schools. The success of student learning depends on how the learning process is experienced by students as students, and teachers as educators who are directly involved in the implementation of learning. To improve the learning process of students, teachers must be able to choose and apply appropriate learning methods to improve student achievement. The research method used in this research is descriptive research with qualitative analysis. active knowledge sharing is a strategy that can bring students of SMA Negeri-1 Manuhing to be ready and active in learning activities. This strategy can be used to see the level of ability of students in learning.